ENVIRONMENTAL DISCLOSURE INFORMATION: THE ROLE OF ENVIRONMENTAL CERTIFICATION AND FIRM SIZE - Maya Indriastuti; Anis Chariri; Fuad Fuad (JRAK, 2022)
Activities disclosure reflects corporate accountability, responsibility, and transparency to investors and other stakeholders. Therefore, the objectives of this study are to analyze and empirically test the effect of the board of directors and the environment certification at 36 mining companies listed on the Indonesia Stock Exchange within 2019-2021 with 108 annual reports. The results of multiple linear regression data processing showed that the board of directors could not increase the amount of environmental disclosure information. Meanwhile, environmental certification and firm size can increase the amount of environmental disclosure information. The implication of this research is companies need to disclose enviromental information in order to gain business trust from the public, investors and other stakeholders.